Polarizing plate with adhesive layer

The polarizing plate with a low-moisture permeability adhesive layer, using polyisobutylene and a hydrogen abstraction photopolymerization initiator, addresses iodine loss in high temperature and humidity, ensuring durability and adhesive strength.

JP7599854B2Active Publication Date: 2024-12-16SUMITOMO CHEM CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2020115808
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-07-03
Publication Date
2024-12-16
Estimated Expiration
2040-07-03

AI Technical Summary

Technical Problem

Polarizing plates experience iodine loss in high temperature and high humidity environments, particularly when a protective film is placed on one side via an adhesive layer, leading to poor moisture and heat resistance.

Method used

A polarizing plate with an adhesive layer comprising a first adhesive layer with moisture permeability of 500 g/(m²·day) or less, made from a rubber-based adhesive containing polyisobutylene and a hydrogen abstraction type photopolymerization initiator, and optionally a second adhesive layer, along with a functional layer such as a liquid crystal cured layer, to enhance durability.

Benefits of technology

The solution effectively suppresses iodine loss in high temperature and high humidity conditions, maintaining the integrity of the polarizing plate by reducing moisture permeability and enhancing adhesive properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007599854000002
    Figure 0007599854000002
  • Figure 0007599854000003
    Figure 0007599854000003
  • Figure 0007599854000004
    Figure 0007599854000004
Patent Text Reader

Abstract

To provide a polarizing plate with an adhesive layer, which minimizes iodine elution even in high-temperature / high-humidity environments.SOLUTION: A polarizing plate 100 with an adhesive layer is provided, comprising a polarizer 10 and a protective film 11 provided on one side of the polarizer via an adhesive layer 12, and also including a second adhesive layer 14, a functional layer 15, and a first adhesive layer 13 provided on the other side of the polarizer in the described order from the polarizer side. The functional layer is either a single layer consisting of a cured liquid crystal layer or a multilayer consisting of two or more layers selected from a group of a cured liquid crystal layer, an alignment layer, and a bonding layer. The polarizer is a hydrophilic polymer film with iodine absorbed therein. The first adhesive layer exhibits a moisture permeability of 500 g / (m2 / day) or less at a temperature of 40°C and relative humidity of 90% RH.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polarizing plate with a pressure-sensitive adhesive layer, and further to an image display device including the same. [Background technology]

[0002] Patent Document 1 proposes a polarizing plate with a pressure-sensitive adhesive layer, in which a polarizer protective film is laminated on one side of a polarizer via an adhesive layer, and a pressure-sensitive adhesive layer is laminated on the other side. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2012-247574 A Summary of the Invention [Problem to be solved by the invention]

[0004] An object of the present invention is to provide a polarizing plate with a pressure-sensitive adhesive layer that is suppressed from losing iodine even in a high-temperature and high-humidity environment. [Means for solving the problem]

[0005] The present invention provides the following pressure-sensitive adhesive layer-attached polarizing plate and image display device. [1] A polarizing plate with a pressure-sensitive adhesive layer, comprising: a polarizer; a protective film disposed on one side of the polarizer via an adhesive layer; and a second pressure-sensitive adhesive layer, a functional layer, and a first pressure-sensitive adhesive layer, in this order, from the polarizer side, on the other side of the polarizer, The functional layer is a single layer of a cured liquid crystal layer alone, or a multilayer of two or more layers selected from the group consisting of a cured liquid crystal layer, an alignment layer, and an attachment layer; the polarizer is a hydrophilic polymer film having iodine adsorbed thereon; The first adhesive layer has a moisture permeability of 500 g / (m 2 1. A polarizing plate with an adhesive layer, the temperature of which is 100° C. or less. [2] The polarizing plate with a pressure-sensitive adhesive layer described in [1], wherein the first and second pressure-sensitive adhesive layers are pressure-sensitive adhesive layers formed from a rubber-based pressure-sensitive adhesive composition containing polyisobutylene and a hydrogen abstraction type photopolymerization initiator. [3] The polarizing plate with a pressure-sensitive adhesive layer according to [1], wherein the first and second pressure-sensitive adhesive layers are pressure-sensitive adhesive layers containing a polyolefin resin. [4] The polarizing plate with a pressure-sensitive adhesive layer according to [3], wherein the polyolefin resin contains an amorphous polypropylene resin. [5] The polarizing plate with a pressure-sensitive adhesive layer according to any one of [1] to [4], wherein the first pressure-sensitive adhesive layer has a thickness of 10 μm or more. [6] The polarizing plate with a pressure-sensitive adhesive layer according to any one of [1] to [5], wherein the protective film is a film made of a cyclic polyolefin resin. [7] The polarizing plate with a pressure-sensitive adhesive layer according to any one of [1] to [6], wherein the functional layer includes a first liquid crystal cured layer and a second liquid crystal cured layer. [8] A laminate for a flexible image display device, comprising the pressure-sensitive adhesive layer-attached polarizing plate according to any one of [1] to [7], and a front panel or a touch sensor. [9] An image display device comprising the pressure-sensitive adhesive layer-attached polarizing plate according to any one of [1] to [7]. Effect of the Invention

[0006] According to the present invention, it is possible to provide a polarizing plate with a pressure-sensitive adhesive layer in which iodine loss is suppressed even in a high-temperature and high-humidity environment. [Brief description of the drawings]

[0007] [Figure 1] 1 is a schematic cross-sectional view showing an example of a pressure-sensitive adhesive layer-attached polarizing plate of the present invention. [Diagram 2] FIG. 2 is a schematic diagram showing a method for installing a sample for evaluating iodine loss. [Diagram 3] 1 is a diagram showing an image of the polarizing plate with a pressure-sensitive adhesive layer obtained in Example 1, observed under an optical microscope. [Figure 4] FIG. 2 is a diagram showing data obtained by converting an observed image of the polarizing plate with a pressure-sensitive adhesive layer obtained in Example 1 into black and white 256 gradations. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] Hereinafter, an embodiment of the present invention will be described with reference to the drawings, but the present invention is not limited to the following embodiment. In all of the drawings, the scale of each component is appropriately adjusted to make it easier to understand, and the scale of each component shown in the drawings does not necessarily match the scale of the actual component.

[0009] <Polarizing plate with adhesive layer> The polarizing plate with a pressure-sensitive adhesive layer includes a polarizer and a protective film disposed on one side of the polarizer via an adhesive layer, and includes, from the polarizer side, a second adhesive layer, a functional layer, and a first adhesive layer in this order on the other side of the polarizer. An example of the layer structure of a polarizing plate with a pressure-sensitive adhesive layer is shown in FIG. 1. FIG. 1 is a schematic cross-sectional view of an example of a polarizing plate with a pressure-sensitive adhesive layer. The polarizing plate with a pressure-sensitive adhesive layer 100 shown in FIG. 1 includes, in this order, a protective film 11, an adhesive layer 12, a polarizer 10, a second adhesive layer 14, a functional layer 15, and a first adhesive layer 13.

[0010] The polarizing plate 100 with a pressure-sensitive adhesive layer is preferably composed only of a protective film 11, an adhesive layer 12, a polarizer 10, a second adhesive layer 14, a functional layer 15, and a first adhesive layer 13. The polarizing plate 100 with a pressure-sensitive adhesive layer preferably has the protective film 11 laminated on one side of the polarizer 10 via only the adhesive layer 12. The polarizing plate 100 with a pressure-sensitive adhesive layer preferably has the second adhesive layer 14 laminated directly on the surface of the polarizer 10 opposite to the adhesive layer 12 side.

[0011] The thickness of the polarizing plate 100 with an adhesive layer is not particularly limited as it varies depending on the function required of the polarizing plate 100 with an adhesive layer and the use of the polarizing plate 100 with an adhesive layer, and may be, for example, 10 μm or more, or 20 μm or more, or may be, for example, 200 μm or less, 150 μm or less, 120 μm or less, 100 μm or less, 80 μm or less, or 70 μm or less.

[0012] [Polarizer] Polarizer 10 has the property of absorbing linearly polarized light having a vibration plane parallel to its absorption axis and transmitting linearly polarized light having a vibration plane perpendicular to the absorption axis (parallel to the transmission axis). Polarizer 10 is a film in which iodine is adsorbed onto a hydrophilic polymer film. Polarizer 10 can be manufactured, for example, through a process of uniaxially stretching a hydrophilic polymer film, a process of dyeing the hydrophilic polymer film with iodine to adsorb the iodine, a process of treating the hydrophilic polymer film with the iodine adsorbed thereon with an aqueous solution of boric acid, and a process of washing with water after the treatment with the aqueous solution of boric acid.

[0013] Examples of hydrophilic polymer films include polyvinyl alcohol resin films. Polyvinyl alcohol resins are obtained by saponifying polyvinyl acetate resins. Examples of polyvinyl acetate resins include polyvinyl acetate, which is a homopolymer of vinyl acetate, and copolymers of vinyl acetate and other monomers copolymerizable therewith. Examples of other monomers copolymerizable with vinyl acetate include unsaturated carboxylic acid compounds, olefin compounds, vinyl ether compounds, unsaturated sulfone compounds, and (meth)acrylamide compounds having an ammonium group. In this specification, "(meth)acrylic" means at least one selected from acrylic and methacrylic. The same applies to "(meth)acrylate" and the like.

[0014] The degree of saponification of the polyvinyl alcohol resin is usually about 85 mol% or more and 100 mol% or less, preferably 98 mol% or more. The polyvinyl alcohol resin may be modified, and polyvinyl formal, polyvinyl acetal, etc. modified with aldehydes can also be used. The degree of polymerization of the polyvinyl alcohol resin is usually 1000 or more and 10000 or less, preferably 1500 or more and 5000 or less.

[0015] The polarizer 10 has iodine adsorbed and aligned, and the boron content is 5.5 mass % or less, preferably 5.0 Mass% or lessBy configuring the boron content to be 0.5% by mass or more, more preferably 4.5% by mass or less, shrinkage caused by heating can be suppressed. The boron content is preferably 0.5% by mass or more, more preferably 1% by mass or more, and may be 2% by mass or more. By configuring the boron content to be 0.5% by mass or more, iodine can be stably retained, and it is expected that discoloration can be suppressed.

[0016] The thickness of the polarizer 10 is usually 30 μm or less, preferably 15 μm or less, more preferably 13 μm or less, and further preferably 10 μm or less. The thickness of the polarizer 10 is usually 2 μm or more, preferably 3 μm or more, and may be, for example, 5 μm or more.

[0017] [Protective film] The protective film 11 is disposed on one side of the polarizer 10 and can have the function of protecting the polarizer 10. The protective film 11 can be a coating layer or a film made of an optically transparent thermoplastic resin, for example, a cyclic polyolefin-based resin; a cellulose acetate-based resin made of a resin such as triacetyl cellulose or diacetyl cellulose; a polyester-based resin made of a resin such as polyethylene terephthalate, polyethylene naphthalate, or polybutylene terephthalate; a polycarbonate-based resin; a (meth)acrylic-based resin; a polypropylene-based resin, or a mixture of one or more of these.

[0018] A hard coat layer may be formed on the protective film 11. The hard coat layer may be formed on one side of the protective film 11 or on both sides. By providing the hard coat layer, the protective film 11 can be improved in hardness and scratch resistance. The hard coat layer may be a cured layer of, for example, an acrylic resin, a silicone resin, a polyester resin, a urethane resin, an amide resin, an epoxy resin, or the like. The hard coat layer may contain an additive to improve strength. The additive is not limited, and examples thereof include inorganic fine particles, organic fine particles, or a mixture thereof. The hard coat layer is, for example, a cured layer of an ultraviolet curing resin. Examples of the ultraviolet curing resin include an acrylic resin, a silicone resin, a polyester resin, a urethane resin, an amide resin, and an epoxy resin.

[0019] The thickness of the protective film 11 is usually 1 μm or more and 100 μm or less, and from the standpoint of strength, handleability, etc., it is preferably 5 μm or more and 80 μm or less, more preferably 8 μm or more and 60 μm or less, even more preferably 12 μm or more and 45 μm or less, and may be 30 μm or less.

[0020] [Adhesive layer] The adhesive layer 12 can be interposed between the protective film 11 and the polarizer 10 to bond them together. Examples of the adhesive forming the adhesive layer 12 include a water-based adhesive, an active energy ray-curable adhesive, and a thermosetting adhesive, and it is preferable to use a water-based adhesive or an active energy ray-curable adhesive. The surfaces of the protective film 11 and the polarizer 10 facing each other to be bonded together via the adhesive layer 12 may be previously subjected to a corona treatment, a plasma treatment, a flame treatment, or the like, and may have a primer layer or the like.

[0021] The thickness of the adhesive layer 12 is usually 0.01 μm or more so that the adhesion between the protective film 11 and the polarizer 10 can be easily ensured, and is usually 10 μm or less.

[0022] [First adhesive layer] The first pressure-sensitive adhesive layer 13 has a moisture permeability (hereinafter, simply referred to as "moisture permeability") of 500 g / (m 2 ·day) or less. The moisture permeability is measured according to the measurement method described in the Examples section below.

[0023] The polarizing plate with an adhesive layer is attached to an organic EL display element or a liquid crystal cell (usually an inorganic glass surface) via the adhesive layer. When the polarizer is a hydrophilic resin film, it tends to have poor moist heat resistance after being attached to an inorganic glass surface, and iodine tends to escape from the end of the polarizer, i.e., so-called iodine escape tends to occur easily. In particular, iodine escape tends to occur easily in a polarizing plate with an adhesive layer in which a protective film is arranged on one side of the polarizer via only an adhesive layer and an adhesive layer is arranged directly on the other side. The polarizing plate with an adhesive layer 100 has a moisture permeability of 500 g / (m 2 ·day), iodine loss tends to be easily suppressed. When protective films are laminated on both sides of the polarizer via adhesive layers (double-sided protected polarizing plate), such iodine loss tends to be less likely to occur.

[0024] The moisture permeability of the first adhesive layer 13 is 400 g / (m 2 ·day) or less, and 300g / (m 2 ·day) or less is more preferable, and 200g / (m 2 ·day) or less. Although there is no particular restriction on the lower limit of the moisture permeability, ideally, the moisture permeability should be such that no moisture permeation is allowed (i.e., 0 g / (m 2 The moisture permeability can be measured according to the method described in the Examples.

[0025] The composition of the adhesive forming the first adhesive layer 13 is not particularly limited, and a layer made of any appropriate adhesive may be used. Examples of adhesives include rubber-based adhesives, polyolefin-based adhesives, acrylic-based adhesives, silicone-based adhesives, urethane-based adhesives, vinyl alkyl ether-based adhesives, polyvinyl alcohol-based adhesives, polyvinyl pyrrolidone-based adhesives, polyacrylamide-based adhesives, and cellulose-based adhesives. Among these, rubber-based adhesives and polyolefin-based adhesives are preferred from the viewpoint of moisture permeability.

[0026] The rubber-based adhesive may be any adhesive containing a rubber-based polymer, and the composition thereof is not particularly limited.

[0027] The rubber-based polymer used in the present invention is a polymer that exhibits rubber elasticity in a temperature range around room temperature. Specifically, styrene-based thermoplastic elastomers, isobutylene-based polymers, etc. can be mentioned, but in the present invention, it is preferable to use polyisobutylene (PIB), which is a homopolymer of isobutylene, from the viewpoint of weather resistance. This is because polyisobutylene does not contain a double bond in the main chain, and therefore has excellent light resistance.

[0028] As the polyisobutylene, for example, a commercially available product such as OPPANOL manufactured by BASF can be used.

[0029] The weight average molecular weight (Mw) of the polyisobutylene is preferably 100,000 or more, more preferably 300,000 or more, even more preferably 600,000 or more, and particularly preferably 700,000 or more. The upper limit of the weight average molecular weight is not particularly limited, but is preferably 5 million or less, more preferably 3 million or less, and even more preferably 2 million or less. By making the weight average molecular weight of the polyisobutylene 100,000 or more, a rubber-based pressure-sensitive adhesive having better durability during high-temperature storage can be obtained.

[0030] The content of the polyisobutylene is not particularly limited, but is preferably 50% by mass or more, more preferably 60% by mass or more, even more preferably 70% by mass or more, even more preferably 80% by mass or more, even more preferably 85% by mass or more, and particularly preferably 90% by mass or more, based on the total solid content of the rubber-based pressure-sensitive adhesive. The upper limit of the content of polyisobutylene is not particularly limited, but is preferably 99% by mass or less, more preferably 98% by mass or less. It is preferable to include polyisobutylene in the above range because it has excellent low moisture permeability.

[0031] The rubber-based adhesive used in the present invention may also contain polymers and elastomers other than the polyisobutylene. Specifically, isobutylene-based polymers such as copolymers of isobutylene and normal butylene, copolymers of isobutylene and isoprene (e.g., butyl rubbers such as regular butyl rubber, chlorinated butyl rubber, brominated butyl rubber, and partially crosslinked butyl rubber), vulcanized products or modified products thereof (e.g., modified with functional groups such as hydroxyl groups, carboxyl groups, amino groups, and epoxy groups); styrene-ethylene-butylene-styrene block copolymers (SEBS), styrene-isoprene-styrene block copolymers (SIS), styrene-butadiene-styrene block copolymers (SBS), styrene-ethylene-propylene-styrene block copolymers (SEPS, hydrogenated products of SIS), styrene-ethylene-propylene block copolymers (SBS ... Examples of suitable thermoplastic elastomers include styrene-based block copolymers such as styrene-isoprene block copolymers (SEP, hydrogenated styrene-isoprene block copolymers), styrene-isobutylene-styrene block copolymers (SIBS), and styrene-butadiene rubber (SBR); butyl rubber (IIR), butadiene rubber (BR), acrylonitrile-butadiene rubber (NBR), EPR (binary ethylene-propylene rubber), EPT (ternary ethylene-propylene rubber), acrylic rubber, urethane rubber, and polyurethane-based thermoplastic elastomers; polyester-based thermoplastic elastomers; and blend-based thermoplastic elastomers such as a polymer blend of polypropylene and EPT (ternary ethylene-propylene rubber). These can be added in an amount not impairing the effects of the present invention, but it is preferable that the amount is about 10 parts by weight or less relative to 100 parts by weight of the polyisobutylene, and it is preferable that they are not included from the viewpoint of durability.

[0032] Furthermore, it is particularly preferable that the rubber-based pressure-sensitive adhesive used in the present invention contains the polyisobutylene and a hydrogen abstraction type photopolymerization initiator.

[0033] The hydrogen abstraction type photopolymerization initiator is capable of abstracting hydrogen from the polyisobutylene and creating reactive sites in the polyisobutylene without cleavage of the initiator itself by irradiation with active energy rays, and is capable of initiating a crosslinking reaction of the polyisobutylene by forming the reactive sites.

[0034] As the photopolymerization initiator, in addition to the hydrogen abstraction type photopolymerization initiator used in the present invention, a cleavage type photopolymerization initiator is also known, in which the photopolymerization initiator itself is cleaved and decomposed to generate radicals by irradiation with active energy rays. However, if a cleavage type photopolymerization initiator is used for the polyisobutylene used in the present invention, the main chain of the polyisobutylene is cut by the photopolymerization initiator that generates radicals, and crosslinking is not possible. In the present invention, by using a hydrogen abstraction type photopolymerization initiator, crosslinking of polyisobutylene can be performed as described above.

[0035] Examples of hydrogen abstraction type photopolymerization initiators include acetophenone, benzophenone, and o-benzoylbenzoic acid. 、Benzophenone compounds such as methyl-4-phenylbenzophenone, 4,4'-dichlorobenzophenone, hydroxybenzophenone, 4,4'-dimethoxybenzophenone, 4,4'-dichlorobenzophenone, 4,4'-dimethylbenzophenone, 4-benzoyl-4'-methyl-diphenyl sulfide, acrylated benzophenone, 3,3',4,4'-tetra(t-butylperoxycarbonyl)benzophenone, and 3,3'-dimethyl-4-methoxybenzophenone; 2-isopropylthioxanthone, 2,4-dimethylthioxanthone, 2,4 Thioxanthone compounds such as thioxanthone, 2,4-dichlorothioxanthone, etc.; aminobenzophenone compounds such as 4,4'-bis(dimethylamino)benzophenone, 4,4'-diethylaminobenzophenone, etc.; 10-butyl-2-chloroacridone, 2-ethylanthraquinone, 9,10-phenanthrenequinone, camphorquinone, etc.; aromatic ketone compounds such as acetonaphthone, 1-hydroxycyclohexylphenyl ketone, etc.; aromatic aldehydes such as terephthalaldehyde, etc., and quinone aromatic compounds such as methylanthraquinone, etc. These can be used alone or in combination of two or more. Among these, benzophenone compounds are preferred from the viewpoint of reactivity, and benzophenone is more preferred.

[0036] The content of the hydrogen abstraction type photopolymerization initiator is preferably 0.001 to 10 parts by mass, more preferably 0.005 to 10 parts by mass, and even more preferably 0.01 to 10 parts by mass, relative to 100 parts by mass of the polyisobutylene. By including the hydrogen abstraction type photopolymerization initiator in the above range, the crosslinking reaction can be progressed to the target density, which is preferable.

[0037] In the present invention, a cleavage type photopolymerization initiator may be used together with the hydrogen abstraction type photopolymerization initiator as long as the effect of the present invention is not impaired. However, it is preferable not to use such a photopolymerization initiator for the reasons described above.

[0038] The rubber-based adhesive used in the present invention may further contain a polyfunctional radical polymerizable compound, which functions as a crosslinking agent for polyisobutylene.

[0039] The polyfunctional radical polymerizable compound is a compound having at least two radically polymerizable functional groups having an unsaturated double bond, such as a (meth)acryloyl group or a vinyl group. Specific examples of the polyfunctional radical polymerizable compound include tripropylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, 2-ethyl-2-butylpropanediol di(meth)acrylate, bisphenol A di(meth)acrylate, bisphenol A ethylene oxide adduct di(meth)acrylate, bisphenol A propylene oxide adduct di(meth)acrylate, bisphenol A diglycidyl ether di(meth)acrylate, ne Examples of the esters of (meth)acrylic acid and polyhydric alcohols such as dipentyl glycol di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, dioxane glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and EO-modified diglycerin tetra(meth)acrylate, and 9,9-bis[4-(2-(meth)acryloyloxyethoxy)phenyl]fluorene, etc. can be mentioned. These can be used alone or as a mixture of two or more. Among these, from the viewpoint of compatibility with polyisobutylene, esters of (meth)acrylic acid and polyhydric alcohols are preferred, difunctional (meth)acrylates having two (meth)acryloyl groups and trifunctional (meth)acrylates having three or more (meth)acryloyl groups are more preferred, and tricyclodecane dimethanol di(meth)acrylate and trimethylolpropane tri(meth)acrylate are particularly preferred.

[0040] The content of the polyfunctional radical polymerizable compound is preferably 20 parts by mass or less, more preferably 15 parts by mass or less, and even more preferably 10 parts by mass or less, relative to 100 parts by mass of the polyisobutylene. The lower limit of the content of the polyfunctional radical polymerizable compound is not particularly limited, but for example, it is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, and even more preferably 1 part by mass or more, relative to 100 parts by mass of the polyisobutylene. The content of the polyfunctional radical polymerizable compound in the above range is preferable from the viewpoint of durability of the obtained rubber-based pressure-sensitive adhesive layer.

[0041] The molecular weight of the polyfunctional radically polymerizable compound is not particularly limited, but is preferably, for example, about 1000 or less, and more preferably about 500 or less.

[0042] The rubber-based adhesive used in the present invention may contain at least one tackifier selected from the group consisting of tackifiers containing a terpene skeleton, tackifiers containing a rosin skeleton, and hydrogenated products thereof. By containing a tackifier in the rubber-based adhesive, it is possible to form a rubber-based adhesive layer that has high adhesion to various adherends and high durability even in high temperature environments, which is preferable.

[0043] Examples of the tackifier containing the terpene skeleton include terpene polymers such as α-pinene polymers, β-pinene polymers, and dipentene polymers, and modified terpene resins obtained by modifying the terpene polymers (phenol-modified, styrene-modified, aromatic-modified, hydrogenated, hydrocarbon-modified, etc.). Examples of the modified terpene resins include terpene phenolic resins, styrene-modified terpene resins, aromatic-modified terpene resins, and hydrogenated terpene resins (hydrogenated terpene resins). Examples of the hydrogenated terpene resins include hydrogenated terpene polymers, other modified terpene resins, and hydrogenated terpene phenolic resins. Among these, hydrogenated terpene phenolic resins are preferred from the viewpoints of compatibility with rubber-based adhesives and adhesive properties.

[0044] Examples of tackifiers containing a rosin skeleton include rosin resins, polymerized rosin resins, hydrogenated rosin resins, rosin ester resins, hydrogenated rosin ester resins, and rosin phenolic resins. Specifically, unmodified rosins (raw rosins) such as gum rosin, wood rosin, and tall oil rosin, modified rosins obtained by hydrogenating, disproportionating, polymerizing, or otherwise chemically modifying these, and derivatives of these can be used.

[0045] As the tackifier, for example, commercially available products such as the Clearon series and Polystar series manufactured by Yasuhara Chemical Co., Ltd., and the Super Ester series, Pencel series, and Pine Crystal series manufactured by Arakawa Chemical Industries, Ltd. can be used.

[0046] When the tackifier is a hydrogenated product, the hydrogenation may be a partial hydrogenation in which only a part of the double bonds in the compound are hydrogenated, or a complete hydrogenation in which all double bonds in the compound are hydrogenated. In the present invention, a complete hydrogenation is preferable from the viewpoints of adhesion properties, weather resistance, and color.

[0047] The tackifier preferably contains a cyclohexanol skeleton from the viewpoint of adhesive properties. Although the detailed principle is unclear, it is considered that the cyclohexanol skeleton is more balanced in compatibility with the base polymer polyisobutylene than the phenol skeleton. As the tackifier containing a cyclohexanol skeleton, for example, hydrogenated products such as terpene phenol resin and rosin phenol resin are preferable, and fully hydrogenated products such as terpene phenol resin and rosin phenol resin are more preferable.

[0048] The softening point (softening temperature) of the tackifier is not particularly limited, but is preferably about 80° C. or higher, and more preferably about 100° C. or higher. The softening point of the tackifier is preferably 80° C. or higher, because the tackifier can maintain its adhesive properties without softening even at high temperatures. The upper limit of the softening point of the tackifier is not particularly limited, but if the softening point is too high, the molecular weight becomes higher, the compatibility deteriorates, and problems such as whitening may occur. Therefore, for example, it is preferably about 200° C. or lower, and more preferably about 180° C. or lower. The softening point of the tackifier resin is defined as a value measured by the softening point test method (ring and ball method) specified in either JIS K5902 or JIS K2207.

[0049] The weight average molecular weight (Mw) of the tackifier is not particularly limited, but is preferably 50,000 or less, preferably 30,000 or less, more preferably 10,000 or less, even more preferably 8,000 or less, and particularly preferably 5,000 or less. The lower limit of the weight average molecular weight of the tackifier is not particularly limited, but is preferably 500 or more, more preferably 1,000 or more, and even more preferably 2,000 or more. The weight average molecular weight of the tackifier within the above range is preferable because it has good compatibility with polyisobutylene and does not cause problems such as whitening.

[0050] The amount of the tackifier added is preferably 40 parts by mass or less, more preferably 30 parts by mass or less, and even more preferably 20 parts by mass or less, relative to 100 parts by mass of the polyisobutylene. The lower limit of the amount of the tackifier added is not particularly limited, but is preferably 0.1 parts by mass or more, more preferably 1 part by mass or more, and even more preferably 5 parts by mass or more. By setting the amount of the tackifier used within the above range, it is preferable because the adhesive properties can be improved. Furthermore, if the amount of the tackifier used exceeds the above range and is added in a large amount, the cohesive strength of the adhesive tends to decrease, which is not preferable.

[0051] In addition, a tackifier other than the tackifier containing a terpene skeleton and the tackifier containing a rosin skeleton may be added to the rubber-based adhesive used in the present invention. Examples of such tackifiers include petroleum resin-based tackifiers. Examples of the petroleum-based tackifiers include aromatic petroleum resins, aliphatic petroleum resins, alicyclic petroleum resins (aliphatic cyclic petroleum resins), aliphatic-aromatic petroleum resins, aliphatic-alicyclic petroleum resins, hydrogenated petroleum resins, coumarone-based resins, and coumarone-indene resins.

[0052] The petroleum resin-based tackifier can be used in an amount that does not impair the effects of the present invention, and can be used, for example, in an amount of about 30 parts by mass or less per 100 parts by mass of the polyisobutylene.

[0053] The rubber-based adhesive may contain an organic solvent as a diluent. The diluent is not particularly limited, but may be, for example, toluene, xylene, n-heptane, dimethyl ether, etc., and may be used alone or in combination of two or more. Among these, toluene is preferred.

[0054] The amount of diluent added is not particularly limited, but is preferably about 50 to 95% by mass, more preferably about 70 to 90% by mass, in the rubber-based pressure-sensitive adhesive. The amount of diluent added within the above range is preferable from the viewpoint of coatability on a support or the like.

[0055] The rubber-based adhesive used in the present invention may contain additives other than those mentioned above, provided that the effect of the present invention is not impaired. Specific examples of additives include softeners, crosslinking agents (e.g., polyisocyanates, epoxy compounds, alkyl etherified melamine compounds, etc.), fillers, antioxidants, and ultraviolet absorbers. The types, combinations, and amounts of additives added to the rubber-based adhesive may be appropriately set according to the purpose. The content (total amount) of the additives in the rubber-based adhesive is preferably 30% by mass or less, more preferably 20% by mass or less, and even more preferably 10% by mass or less.

[0056] The rubber-based adhesive layer used in the present invention can be formed from the rubber-based adhesive, and the manufacturing method thereof is not particularly limited. The adhesive layer can be formed by applying the rubber-based adhesive to various supports or the like, and then drying by heating or irradiating with active energy rays, or the like.

[0057] When the rubber-based adhesive contains polyisobutylene, it is preferable to irradiate the rubber-based adhesive with active energy rays to crosslink the polyisobutylene. The active energy rays are usually irradiated to the coating layer obtained by applying the rubber-based adhesive to various supports. The active energy rays may be directly irradiated to the coating layer (without laminating other members, etc.), or may be irradiated after laminating various members such as an optical film such as a separator or glass to the coating layer. When irradiating after laminating to the optical film or various members, the active energy rays may be irradiated through the optical film or various members, or the optical film or various members may be peeled off and the active energy rays may be irradiated from the peeled surface.

[0058] The rubber-based pressure-sensitive adhesive can be applied by various methods, specifically, for example, roll coating, kiss roll coating, gravure coating, reverse coating, roll brushing, spray coating, dip roll coating, bar coating, knife coating, air knife coating, curtain coating, lip coating, extrusion coating using a die coater, etc.

[0059] When the coating layer of the rubber-based adhesive is dried by heating, the heating and drying temperature is preferably about 30°C to 200°C, more preferably 40°C to 180°C, and even more preferably 80°C to 150°C. By setting the heating temperature within the above range, a rubber-based adhesive layer having excellent adhesive properties can be obtained. The drying time can be appropriately selected. The drying time is preferably about 5 seconds to 20 minutes, more preferably 30 seconds to 10 minutes, and even more preferably 1 minute to 8 minutes.

[0060] Furthermore, even when the coating layer of the rubber-based pressure-sensitive adhesive is irradiated with active energy rays, if the adhesive or pressure-sensitive adhesive contains an organic solvent as a diluent, it is preferable to remove the solvent, etc. by heating and drying or the like after coating and before irradiation with active energy rays.

[0061] The heating and drying temperature is not particularly limited, but from the viewpoint of reducing the amount of residual solvent, it is preferably about 30° C. to 90° C., and more preferably about 60° C. to 80° C. The drying time can be appropriately selected. The drying time is preferably about 5 seconds to 20 minutes, more preferably 30 seconds to 10 minutes, and even more preferably 1 minute to 8 minutes.

[0062] Examples of the active energy rays include visible light, ultraviolet light, and electron beams, with ultraviolet light being preferred among these.

[0063] The conditions for the ultraviolet irradiation are not particularly limited and can be set to any appropriate conditions depending on the composition of the rubber-based adhesive to be crosslinked. For example, the cumulative irradiation amount is 100 mJ / cm 2 ~2000mJ / cm 2 is preferred.

[0064] As the support, for example, a release-treated sheet (separator) can be used.

[0065] Examples of materials constituting the separator include plastic films such as polyethylene, polypropylene, polyethylene terephthalate, and polyester films; porous materials such as paper, cloth, and nonwoven fabrics; and appropriate thin materials such as nets, foam sheets, metal foils, and laminates thereof. Plastic films are preferably used because of their excellent surface smoothness.

[0066] Examples of the plastic film include a polyethylene film, a polypropylene film, a polybutene film, a polybutadiene film, a polymethylpentene film, a polyvinyl chloride film, a vinyl chloride copolymer film, a polyethylene terephthalate film, a polybutylene terephthalate film, a polyurethane film, and an ethylene-vinyl acetate copolymer film.

[0067] The thickness of the separator is usually 5 to 200 μm, preferably about 5 to 100 μm. The separator may be treated with a silicone-based, fluorine-based, long-chain alkyl-based or fatty acid amide-based release agent, a release agent such as silica powder, an antifouling agent, or an antistatic treatment such as a coating type, a kneading type or a deposition type. In particular, by appropriately performing a release treatment such as a silicone treatment, a long-chain alkyl treatment or a fluorine treatment on the surface of the separator, the releasability from the pressure-sensitive adhesive layer can be further improved.

[0068] When the rubber-based pressure-sensitive adhesive layer is formed on a release-treated sheet (separator), the rubber-based pressure-sensitive adhesive layer functions as a on the layer The pressure-sensitive adhesive layer-attached polarizing plate of the present invention can be formed by transferring the pressure-sensitive adhesive layer onto the substrate.

[0069] The gel fraction of the rubber-based pressure-sensitive adhesive layer used in the present invention is not particularly limited, but is preferably about 10 to 98%, more preferably about 25 to 98%, and even more preferably about 45 to 90%. The gel fraction in the above range is preferable because it can achieve both durability and adhesive strength.

[0070] The polyolefin-based pressure-sensitive adhesive may be any adhesive containing a polyolefin-based resin, and the composition thereof is not particularly limited.

[0071] Specific examples of polyolefin resins include low-density polyethylene, very low-density polyethylene, low-crystalline polypropylene, amorphous propylene-(1-butene) copolymer, ionomer resin, ethylene copolymers such as ethylene-vinyl acetate copolymer, ethylene-(meth)acrylic acid copolymer, ethylene-(meth)acrylic acid ester-maleic anhydride copolymer, and ethylene-glycidyl methacrylate copolymer, and polyolefin-modified polymers. The adhesive layer containing a polyolefin resin (hereinafter also referred to as a polyolefin adhesive layer) more preferably contains an amorphous polypropylene resin, and more preferably contains an amorphous propylene-(1-butene) copolymer. Such a polyolefin adhesive layer can provide an adhesive sheet with even better step-following properties. In this specification, "amorphous" refers to a property that does not have a clear melting point like a crystalline substance.

[0072] The content of the amorphous propylene-(1-butene) copolymer in the polyolefin-based pressure-sensitive adhesive can be appropriately adjusted so that the elasticity of the polyolefin-based pressure-sensitive adhesive layer is 0.7 N / mm or less. The content of the amorphous propylene-(1-butene) copolymer in the polyolefin-based pressure-sensitive adhesive is, in mass ratio, preferably 10 mass% to 100 mass%, more preferably 10 mass% to 95 mass%.

[0073] The amorphous propylene-(1-butene) copolymer can be obtained by polymerizing propylene and 1-butene, preferably using a metallocene catalyst. More specifically, the amorphous propylene-(1-butene) copolymer can be obtained, for example, by performing a polymerization step of polymerizing propylene and 1-butene using a metallocene catalyst, and performing post-treatment steps such as a catalyst residue removal step and a foreign matter removal step after the polymerization step. The amorphous propylene-(1-butene) copolymer is obtained through such steps in the form of, for example, powder or pellet. Examples of the metallocene catalyst include a metallocene homogeneous mixed catalyst containing a metallocene compound and an aluminoxane, and a metallocene supported catalyst in which a metallocene compound is supported on a fine particle carrier.

[0074] The amorphous propylene-(1-butene) copolymer polymerized using a metallocene catalyst as described above exhibits a narrow molecular weight distribution. The molecular weight distribution (Mw / Mn) of the amorphous propylene-(1-butene) copolymer is preferably 3 or less, more preferably 2 or less, even more preferably 1.1 to 2, and particularly preferably 1.2 to 1.9. Since an amorphous propylene-(1-butene) copolymer having a narrow molecular weight distribution contains few low molecular weight components, the use of such an amorphous propylene-(1-butene) copolymer makes it possible to obtain a polyolefin-based pressure-sensitive adhesive layer that can prevent contamination of the adherend due to bleeding of low molecular weight components.

[0075] The content of propylene-derived structural units in the above-mentioned amorphous propylene-(1-butene) copolymer is preferably 80 mol % to 99 mol %, more preferably 85 mol % to 99 mol %, and even more preferably 90 mol % to 99 mol %.

[0076] The content of the 1-butene-derived structural unit in the amorphous propylene-(1-butene) copolymer is preferably 1 mol% to 20 mol%, more preferably 1 mol% to 15 mol%, and even more preferably 1 mol% to 10 mol%. Within this range, a pressure-sensitive adhesive layer having an excellent balance between toughness and flexibility can be obtained.

[0077] The amorphous propylene-(1-butene) copolymer may be a block copolymer or a random copolymer.

[0078] The weight average molecular weight (Mw) of the amorphous propylene-(1-butene) copolymer is preferably 200,000 or more, more preferably 200,000 to 500,000, and even more preferably 200,000 to 300,000. When the weight average molecular weight (Mw) of the amorphous propylene-(1-butene) copolymer is within such a range, a pressure-sensitive adhesive layer that has less low molecular weight components and can prevent contamination of the adherend can be obtained, compared with general styrene-based thermoplastic resins and acrylic-based thermoplastic resins (Mw of 100,000 or less).

[0079] The melt flow rate of the amorphous propylene-(1-butene) copolymer at 230° C. and 2.16 kgf is preferably 1 g / 10 min to 50 g / 10 min, more preferably 5 g / 10 min to 30 g / 10 min, and even more preferably 5 g / 10 min to 20 g / 10 min. If the melt flow rate of the amorphous propylene-(1-butene) copolymer is within this range, a pressure-sensitive adhesive layer of uniform thickness can be formed by coextrusion molding without processing defects. The melt flow rate can be measured by a method according to JIS K7210.

[0080] The amorphous propylene-(1-butene) copolymer may further contain structural units derived from other monomers, as long as the effects of the present invention are not impaired. Examples of the other monomers include α-olefins such as ethylene, 1-pentene, 1-hexene, 1-octene, 1-decene, 4-methyl-1-pentene, and 3-methyl-1-pentene.

[0082] The pressure-sensitive adhesive layer preferably further contains a crystalline polypropylene-based resin. By containing the crystalline polypropylene-based resin, the elastic modulus E' of the pressure-sensitive adhesive layer at 70°C can be adjusted to a desired value. The content of the crystalline polypropylene-based resin can be set to any appropriate ratio depending on the desired elastic modulus E'. The content of the crystalline polypropylene-based resin is preferably 0% by mass to 90% by mass, more preferably 5% by mass to 90% by mass, based on the total weight of the amorphous propylene-(1-butene) copolymer and the crystalline polypropylene-based resin.

[0083] The crystalline polypropylene resin may be a homopolypropylene or a copolymer obtained from propylene and a monomer copolymerizable with propylene. Examples of the monomer copolymerizable with propylene include α-olefins such as ethylene, 1-pentene, 1-hexene, 1-octene, 1-decene, 4-methyl-1-pentene, and 3-methyl-1-pentene. When the crystalline polypropylene resin is a copolymer obtained from propylene and a monomer copolymerizable with propylene, it may be a random copolymer or a block copolymer.

[0084] The crystalline polypropylene resin is preferably obtained by polymerization using a metallocene catalyst, as in the case of the amorphous propylene-(1-butene) copolymer. The use of the crystalline polypropylene resin thus obtained can prevent contamination of the adherend due to bleeding of low molecular weight components.

[0085] The crystallinity of the crystalline polypropylene resin is preferably 10% or more, more preferably 20% or more. The crystallinity is typically determined by differential scanning calorimetry (DSC) or X-ray diffraction.

[0086] Preferably, the polyolefin-based pressure-sensitive adhesive layer is - , Cl - , Br - , NO2 - , NO3 - , SO4 2-, Li + , Na + , K + , Mg 2+ , Ca 2+ , NH4 + This is because it is possible to prevent the adherend from being contaminated by the ions. Adhesive The adhesive layer can be obtained, for example, by solution polymerization of the amorphous propylene-(1-butene) copolymer contained in the polyolefin-based pressure-sensitive adhesive layer using a metallocene catalyst as described above. In the solution polymerization using the metallocene catalyst, the amorphous propylene-(1-butene) copolymer can be purified by repeated precipitation isolation (reprecipitation method) using a poor solvent different from the polymerization solvent, so that a polyolefin-based pressure-sensitive adhesive layer free of the above ions can be obtained. In this specification, the term "F - , Cl - , Br - , NO2 - , NO3 - , SO4 2- , Li + , Na + , K + , Mg 2+ , Ca 2+ , NH4 + "Substantially free of" means that the amount of F is below the detection limit in a standard ion chromatographic analysis (for example, ion chromatographic analysis using Dionex Corporation's product names "DX-320" and "DX-500"). Specifically, F is less than the detection limit in 1 g of the polyolefin-based pressure-sensitive adhesive layer. - , Cl - , Br - , NO2 - , NO3 - , SO4 2- and K. + 0.49μg or less, Li + and Na + Each is 0.20μg or less, Mg 2+ and Ca 2+ were 0.97μg or less, and NH4 + This refers to the case where the amount is 0.5 μg or less.

[0087] The method for producing the polyolefin-based pressure-sensitive adhesive layer is the same as that described above for the method for producing the rubber-based pressure-sensitive adhesive layer.

[0088] The first adhesive layer 13 may further contain other additives within a range that does not impair the effects of the present invention. Examples of the additives include antioxidants, ultraviolet absorbers, light stabilizers, heat stabilizers, antistatic agents, solvents, crosslinking catalysts, tackifiers, plasticizers, softeners, pigments, inorganic fillers, and organic fillers. The type and amount of additives used may be appropriately selected depending on the purpose. These additives may be used alone or in combination of two or more.

[0089] The thickness of the first pressure-sensitive adhesive layer 13 is not particularly limited and can be appropriately set depending on the application, but may be, for example, 250 μm or less, and from the viewpoint of thinning, is preferably 100 μm or less, more preferably 50 μm or less, even more preferably 40 μm or less, particularly preferably 30 μm or less, and even more particularly preferably 27 μm or less. The lower limit of the thickness of the first pressure-sensitive adhesive layer 13 is not particularly limited, but from the viewpoint of durability, it may be, for example, 1 μm or more, preferably 5 μm or more, more preferably 10 μm or more, even more preferably 15 μm or more, and particularly preferably 20 μm or more.

[0090] [Second adhesive layer] The second adhesive layer 14 is interposed between the polarizer 10 and the functional layer 15, and can bond the polarizer 10 and the functional layer 15 together. The second adhesive layer 14 may be composed of an adhesive composition similar to that forming the first adhesive layer 13, or may be composed of an adhesive composition (hereinafter also referred to as the "second adhesive composition") mainly composed of a resin such as a (meth)acrylic, rubber, urethane, ester, silicone, or polyvinyl ether resin. As the second adhesive composition, an adhesive composition having a (meth)acrylic resin as a base polymer, which is excellent in transparency, weather resistance, heat resistance, etc., is preferable. The second adhesive composition may be an active energy ray curable type or a heat curable type.

[0091] The thickness of the second pressure-sensitive adhesive layer 14 may be, for example, 2 μm or more and 30 μm or less, and preferably 3 μm or more and 20 μm or less. For example, it may be 10 μm or more, but from the viewpoint of further reducing the thickness, it is preferably 15 μm or less, more preferably 10 μm or less, and particularly preferably 7 μm or less.

[0092] [Functional Layer] The functional layer 15 is a single layer of a cured liquid crystal layer alone, or a multilayer of two or more layers selected from the group consisting of a cured liquid crystal layer, an alignment layer, and an attachment layer. The functional layer 15 preferably includes two cured liquid crystal layers, and more preferably includes a layer structure in which two cured liquid crystal layers are laminated via an attachment layer.

[0093] [Liquid crystal hardening layer] The liquid crystal cured layer may be a retardation layer made of a cured product of a polymerizable liquid crystal compound, which is formed by applying and aligning a polymerizable liquid crystal compound on a substrate to exhibit optical anisotropy. Examples of the retardation layer made of a cured product of a polymerizable liquid crystal compound include the first to fifth forms. First form: A retardation layer in which rod-shaped liquid crystal compounds are aligned horizontally to the supporting substrate Second type: A retardation layer in which rod-shaped liquid crystal compounds are aligned perpendicular to the substrate Third form: A retardation layer in which the direction of the rod-shaped liquid crystal molecules changes in a helical manner in the plane. Fourth form: Retardation layer in which discotic liquid crystal compounds are tilted Fifth form: A biaxial retardation layer in which discotic liquid crystal compounds are aligned perpendicular to the substrate For example, as an optical film used in an organic electroluminescence display, the first, second, or fifth embodiment is preferably used. Alternatively, retardation layers of these embodiments may be laminated and used.

[0094] When the retardation layer is a layer made of a polymer in an oriented state of a polymerizable liquid crystal compound (hereinafter, sometimes referred to as an "optically anisotropic layer"), the retardation layer preferably has reverse wavelength dispersion. Reverse wavelength dispersion is an optical property in which the liquid crystal alignment in-plane retardation value at a short wavelength is smaller than the liquid crystal alignment in-plane retardation value at a long wavelength, and preferably, the retardation film satisfies the following formulas (1) and (2). Here, Re(λ) represents the in-plane retardation value for light with a wavelength of λ nm. Re(450) / Re(550)≦1 (1) 1≦Re(630) / Re(550) (2) When the retardation layer is in the first form and has reverse wavelength dispersion, coloring during black display in a display device is reduced, which is preferable, and in the formula (1), 0.82≦Re(450) / Re(550)≦0.93 is more preferable. Further, 120≦Re(550)≦150 is more preferable.

[0095] Examples of the polymerizable liquid crystal compound used in the formation of the retardation layer include compounds having a polymerizable group among the compounds described in "3.8.6 Network (completely crosslinked type)" and "6.5.1 Liquid crystal material b. Polymerizable nematic liquid crystal material" in Liquid Crystal Handbook (edited by Liquid Crystal Handbook Editorial Committee, published by Maruzen Co., Ltd. on October 30, 2000), as well as the polymerizable liquid crystal compounds described in JP 2010-31223 A, JP 2010-270108 A, JP 2011-6360 A, JP 2011-207765 A, JP 2011-162678 A, JP 2016-81035 A, International Publication No. 2017 / 043438 A and JP 2011-207765 A. Examples of a method for producing a retardation layer from a polymer in an aligned state of a polymerizable liquid crystal compound include the method described in JP-A-2010-31223.

[0096] The thickness of the retardation layer, which is a liquid crystal cured layer obtained by curing a polymerizable liquid crystal compound, is, for example, 0.1 μm to 10 μm, preferably 0.5 μm to 8 μm, and more preferably 1 μm to 6 μm.

[0097] The retardation layer can be a λ / 4 retardation layer that imparts a retardation of 1 / 4 wavelength to transmitted light, a λ / 2 retardation layer that imparts a retardation of 1 / 2 wavelength to transmitted light, a positive A plate, or a positive C plate. The functional layer can include two liquid crystal hardened layers. When the functional layer includes a first liquid crystal hardened layer and a second liquid crystal hardened layer, the combination of the liquid crystal hardened layers can be a combination of a λ / 2 retardation layer and a λ / 4 retardation layer, a combination of a λ / 4 retardation layer and a positive C layer, etc.

[0098] The pressure-sensitive adhesive layer-attached polarizing plate 100 may be configured as a circular polarizing plate having a λ / 4 retardation layer. The circular polarizing plate can be used as an anti-reflection polarizing plate.

[0099] [Alignment layer] The alignment layer can be disposed between the substrate and the layer of the cured polymerizable liquid crystal compound. The alignment layer has an alignment regulating force that causes the liquid crystal cured layer formed thereon to be aligned in a desired direction. Examples of the alignment layer include an alignment polymer layer formed from an alignment polymer, a photoalignment polymer layer formed from a photoalignment polymer, and a groove alignment film having a concave-convex pattern or a plurality of grooves on the layer surface. The thickness of the alignment layer may be, for example, 10 nm or more and 500 nm or less, and is preferably 10 nm or more and 200 nm or less.

[0100] The oriented polymer layer can be formed by applying a composition in which an oriented polymer is dissolved in a solvent to a substrate, removing the solvent, and performing a rubbing treatment as necessary. In this case, the orientation control force of the oriented polymer layer formed of the oriented polymer can be arbitrarily adjusted by the surface state of the oriented polymer and the rubbing conditions.

[0101] The photo-alignable polymer layer can be formed by applying a composition containing a polymer or monomer having a photoreactive group and a solvent to a substrate layer, and irradiating the composition with polarized light. In this case, the alignment control force of the photo-alignable polymer layer can be arbitrarily adjusted by the conditions of irradiating the photo-alignable polymer with polarized light, etc.

[0102] The groove alignment film can be formed, for example, by a method of forming a concave-convex pattern by exposing the surface of a photosensitive polyimide film through an exposure mask having slits in a pattern shape, developing, etc., a method of forming an uncured layer of active energy ray curable resin on a plate-shaped master having grooves on its surface, transferring this layer to a substrate, and curing the layer, or a method of forming an uncured layer of active energy ray curable resin on a substrate, and pressing a roll-shaped master having concave-convex shapes against this layer to form concave-convex shapes and then curing the layer.

[0103] [Lamination layer] The bonding layer can be arranged to bond the two layers. The bonding layer can be made of an adhesive or a pressure sensitive adhesive. When the functional layer 15 includes two layers of cured liquid crystal layers, the two layers of cured liquid crystal layers can be bonded by the bonding layer.

[0104] The adhesive layer may be made of a water-based adhesive, an active energy ray curable adhesive, a thermosetting adhesive, etc. The thickness of the adhesive layer 12 is from 0.01 μm to 10 μm in order to ensure bonding properties.

[0105] The adhesive may be composed of the same adhesive composition as the adhesive composition forming the first and second adhesive layers, or may be composed of an adhesive composition mainly composed of a resin such as a (meth)acrylic, rubber, urethane, ester, silicone, or polyvinyl ether resin (hereinafter also referred to as the "third adhesive composition"). As the third adhesive composition, an adhesive composition having a (meth)acrylic resin as a base polymer, which is excellent in transparency, weather resistance, heat resistance, etc., is suitable. The third adhesive composition may be an active energy ray curable type or a heat curable type. The thickness of the third adhesive layer is usually 0.1 μm or more and 150 μm or less, for example, 8 μm or more and 60 μm or less, and from the viewpoint of thinning, it is preferably 30 μm or less, and more preferably 20 μm or less. The thickness of the third adhesive layer may be, for example, 10 μm or more, but from the viewpoint of further thinning, it is 15 μm or less, preferably 10 μm or less, and particularly preferably 7 μm or less.

[0106] [Other layers] The polarizing plate 100 with an adhesive layer may include, as other layers, a protective film for protecting the surface (such as the surface of the protective film 11) and a separator film (hereinafter also referred to as a separator) laminated on the outer surface of the first adhesive layer 13.

[0107] [Protection film] For example, after a polarizing plate is attached to an image display element or other optical member, the protective film is peeled off and removed together with the adhesive layer that the protective film has.

[0108] The protective film is, for example, composed of a base film and an adhesive layer laminated thereon. The adhesive layer is as described above. The resin constituting the base film may be, for example, a thermoplastic resin such as a polyethylene-based resin such as polyethylene, a polypropylene-based resin such as polypropylene, a polyester-based resin such as polyethylene terephthalate or polyethylene naphthalate, or a polycarbonate-based resin. A polyester-based resin such as polyethylene terephthalate is preferred.

[0109] [Separate film] The separate film may be a film made of a polyethylene-based resin such as polyethylene, a polypropylene-based resin such as polypropylene, a polyester-based resin such as polyethylene terephthalate, or the like. Among them, a stretched film of polyethylene terephthalate is preferable. The separate film may have a release treatment applied to its surface.

[0110] [Method of manufacturing a polarizing plate with an adhesive layer] The polarizing plate 100 with the adhesive layer can be manufactured, for example, as follows. First, the polarizer 10 and the protective film 11 are laminated via the adhesive layer 12. The polarizing plate may be manufactured by preparing long members, laminating the respective members by roll-to-roll and then cutting them into a predetermined shape, or by cutting the respective members into a predetermined shape and laminating them together. 1After lamination, a heating step or a humidity adjustment step may be performed.

[0111] When the functional layer 15 is a retardation layer, it can be manufactured, for example, as follows. An alignment film is formed on a substrate, and a coating liquid containing a polymerizable liquid crystal compound is applied on the alignment film. In a state where the polymerizable liquid crystal compound is aligned, active energy rays are irradiated to harden the polymerizable liquid crystal compound. A first adhesive layer 13 formed on a release film is laminated on the layer of the hardened polymerizable liquid crystal compound. Then, the substrate and / or the alignment film are peeled off. Then, a second adhesive layer 14 formed on a release film is laminated on the polarizer 10. The retardation layer may be manufactured by preparing long members, laminating the respective members by roll-to-roll and then cutting them into a predetermined shape, or by laminating the respective members after cutting them into a predetermined shape.

[0112] Then, the release film laminated on the second adhesive layer 14 is peeled off, and the functional layer 15 and the polarizer 10 are bonded together via the second adhesive layer 14, thereby producing a polarizing plate 100 with an adhesive layer.

[0113] <Image display device> The polarizing plate 100 with the adhesive layer is disposed on the front surface (viewing side) of an image display panel and can be used as a component of an image display device. If the polarizing plate with the adhesive layer is a circular polarizing plate, it can also be used as an anti-reflection polarizing plate that imparts an anti-reflection function to an image display device. The image display device is not particularly limited, and examples thereof include image display devices such as organic electroluminescence (organic EL) display devices, inorganic electroluminescence (inorganic EL) display devices, liquid crystal display devices, and electroluminescence display devices.

[0114] [Flexible image display device] The image display device may be a flexible image display device. The flexible image display device includes a laminate for a flexible image display device, which will be described later, and an organic EL display panel, and is configured to be bendable, with the laminate for a flexible image display device being disposed on the viewing side of the organic EL display panel.

[0115] <Laminate for flexible image display devices> The laminate for flexible image display device includes the polarizing plate with the adhesive layer of the present invention, and a front plate or a touch sensor. The laminate order of the polarizing plate with the adhesive layer of the present invention, the front plate, and the touch sensor may be, for example, from the viewing side, the front plate, the polarizing plate with the adhesive layer of the present invention, and the touch sensor. The laminate order is preferably the front plate, the touch sensor, and the polarizing plate with the adhesive layer of the present invention. If the polarizing plate is present on the viewing side of the touch sensor, the pattern of the touch sensor is less visible, which is preferable because the visibility of the displayed image is improved. Each member can be laminated using an adhesive, an adhesive, or the like. In addition, the laminate for flexible image display device can be provided with a light-shielding pattern formed on at least one surface of any one of the layers of the front plate, the polarizing plate, and the touch sensor.

[0116] [Front plate] A front plate may be disposed on the viewing side of the polarizing plate. The front plate can be laminated to the polarizing plate via an adhesive layer. Examples of the adhesive layer include the above-mentioned pressure-sensitive adhesive layer and adhesive layer.

[0117] Examples of the front plate include glass and resin film having a hard coat layer on at least one side. As the glass, for example, highly transparent glass or reinforced glass can be used. In particular, when a thin transparent surface material is used, chemically reinforced glass is preferable. The thickness of the glass can be, for example, 100 μm to 5 mm.

[0118] A front panel comprising a hard coat layer on at least one side of a resin film can have flexible properties, unlike the rigidity of existing glass. The thickness of the hard coat layer is not particularly limited, and may be, for example, 5 to 100 μm.

[0119] The resin film may be a film formed of a polymer such as a cycloolefin derivative having a unit of a monomer containing a cycloolefin such as norbornene or a polycyclic norbornene monomer, cellulose (diacetyl cellulose, triacetyl cellulose, acetyl cellulose butyrate, isobutyl ester cellulose, propionyl cellulose, butyryl cellulose, acetyl propionyl cellulose), ethylene-vinyl acetate copolymer, polycycloolefin, polyester, polystyrene, polyamide, polyetherimide, polyacrylic, polyimide, polyamideimide, polyethersulfone, polysulfone, polyethylene, polypropylene, polymethylpentene, polyvinyl chloride, polyvinylidene chloride, polyvinyl alcohol, polyvinyl acetal, polyether ketone, polyether ether ketone, polyethersulfone, polymethyl methacrylate, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polycarbonate, polyurethane, or epoxy. The resin film may be an unstretched, uniaxially or biaxially stretched film. Each of these polymers may be used alone or in a mixture of two or more. As the resin film, preferred are polyamideimide film or polyimide film having excellent transparency and heat resistance, uniaxially or biaxially stretched polyester film, cycloolefin derivative film having excellent transparency and heat resistance and capable of handling large-sized films, polymethyl methacrylate film, and triacetyl cellulose and isobutyl ester cellulose films having no transparency and no optical anisotropy. The thickness of the resin film may be 5 to 200 μm, preferably 20 to 100 μm.

[0120] [Shading pattern] The light-shielding pattern (bezel) is formed on at least one surface of any of the front plate, the polarizing plate, and the touch sensor constituting the laminate for flexible image display devices. For example, it can be formed on the display element side of the front plate. The light-shielding pattern can hide each wiring of the display device so that it is not visible to the user. The color and material of the light-shielding pattern are not particularly limited, and it can be formed of a resin material having various colors such as black, white, and gold. In one embodiment, the thickness of the light-shielding pattern may be in the range of 2 μm to 50 μm, preferably 4 μm to 30 μm, and more preferably 6 μm to 15 μm. In addition, a shape can be given to the light-shielding pattern in order to suppress the inclusion of air bubbles and the visibility of the boundary due to the step between the light-shielding pattern and the display part.

[0121] [Touch sensor] The touch sensor is used as an input means. Various types of touch sensors have been proposed, such as a resistive film type, a surface acoustic wave type, an infrared type, an electromagnetic induction type, and a capacitance type, and any type may be used. Among them, the capacitance type is preferable. The capacitance type touch sensor is divided into an active area and a non-active area located on the outer periphery of the active area. The active area is an area corresponding to an area (display area) where a screen is displayed on a display panel, and is an area where a user's touch is sensed, and the non-active area is an area corresponding to an area (non-display area) where a screen is not displayed on a display device. The touch sensor may include a substrate having a flexible characteristic; a sensing pattern formed in the active area of ​​the substrate; and each sensing line formed in the non-active area of ​​the substrate for connecting to an external driving circuit via the sensing pattern and a pad part. The substrate having a flexible characteristic may be made of the same material as the transparent substrate of the front plate. The substrate of the touch sensor is preferably one having a toughness of 2,000 MPa% or more from the viewpoint of suppressing cracks that may occur in the touch sensor. More preferably, the toughness is 2,000 MPa% to 30,000 MPa%. Here, toughness is defined as the area under the curve up to the breaking point in a stress (MPa)-strain (%) curve obtained through a tensile test of a polymer material. EXAMPLES

[0122] The present invention will be described in more detail below with reference to examples. In the examples, "%" and "parts" are by mass % and parts by mass unless otherwise specified.

[0123] [Moisture permeability] Test materials: Moisture permeability is 70000g / (m 2 The test material was prepared by laminating the first adhesive layer alone onto the surface of a backing (layer) having a viscosity of more than 1.5 μm (days). Moisture permeability measurement method: A water vapor transmission meter (Systech Illinois (UK) "Lyssy80-4000", compliant with JIS K7129-1:2019 (humidity sensor method)) was used to measure the humidity in the 0.07 to 51 cm2 area. 2 Under conditions of a permeation cell temperature of 40°C and a relative humidity of 90% in the high humidity chamber, the measurement start threshold on the low humidity chamber side was set to a relative humidity of 9.7% and the measurement was started. The time required for the relative humidity in the low humidity chamber to change from 9.9% RH to 10.1% RH was measured and the moisture permeability was calculated as water vapor transmission rate.

[0124] [Evaluation of iodine loss] As shown in FIG. 2, the polarizing plate with the adhesive layer was cut into a rectangle of 120 mm (L2) × 60 mm (L1) so that the angle α of the absorption axis T of the polarizer with respect to the long side L2 was 45° when the protective film A side (A side) was placed on the upper side, and the plate was laminated to an alkali-free glass plate (manufactured by Corning, product name "Eagle-XG"), and then left for 504 hours in an environment of a temperature of 65°C and a humidity of 90%RH. Thereafter, a polarizing plate in a cross-Nicol relationship was laminated to the alkali-free glass surface opposite to the tested polarizing plate with the adhesive layer, and the observed image was stored. The optical microscope used was "VHX-500" manufactured by Keyence Corporation. FIG. 3 shows an example of an observation image of the polarizing plate with the adhesive layer observed in this way with an optical microscope. This observation image is an observation image of a polarizing plate with an adhesive layer obtained by Example 1 described later. In Figure 3, when observing along the straight line indicated by the arrow from the edge 50 of the polarizing plate with an adhesive layer inward (the straight line drawn in white perpendicularly from the edge 50), it can be seen that there are iodine-free regions 51 and regions where iodine-free has not occurred (non-iodine-free regions) 52.

[0125] [Measurement of iodine loss by image processing] The image observed under a microscope shown in FIG. 3 is a gray image converted to 256 grayscale levels (0 to 255) using the image analysis software "ImageJ (free software)". The method of converting to 256 grayscale levels (0 to 255) was to take the average of RGB values. FIG. 4 shows profile data in which the grayscale levels are plotted along the straight line drawn in white for the observed image after conversion to 256 grayscale levels shown in FIG. 3. The midpoint (the middle of the iodine-free gradation) between the iodine-free region 51 and the non-iodine-free region 52 in the grayscale profile in the direction perpendicular to the edge 50 of the polarizing plate with an adhesive layer (arrow in FIG. 3) was taken as the iodine-free edge of the polarizing plate with an adhesive layer (FIG. 4), and the distance (μm) from the edge 50 of the polarizing plate with an adhesive layer to the iodine-free edge was measured as the iodine-free distance. The iodine-free distance of the polarizing plate with an adhesive layer is shown in Table 1. The smaller the iodine-free distance, the narrower the iodine-free range and the better the resistance to moisture and heat.

[0126] [Single-sided protective polarizing plate] (Preparation of polarizer) A polyvinyl alcohol film having a thickness of 20 μm, a degree of polymerization of 2400, and a degree of saponification of 99% or more was uniaxially stretched to a stretching ratio of 4.1 times on a heated roll and, while maintaining the tension, was immersed for 60 seconds at 28° C. in a dye bath containing 0.05 parts by mass of iodine and 5 parts by mass of potassium iodide per 100 parts by mass of water.

[0127] Next, the film was immersed in boric acid aqueous solution 1 containing 5.5 parts by mass of boric acid and 15 parts by mass of potassium iodide per 100 parts by mass of water at 64°C for 110 seconds. Next, the film was immersed in boric acid aqueous solution 2 containing 5.5 parts by mass of boric acid and 15 parts by mass of potassium iodide per 100 parts by mass of water at 67°C for 30 seconds. Thereafter, the film was washed with pure water at 10°C and dried to obtain a polarizer. The obtained polarizer had a thickness of 8 μm and a boron content of 4.3 wt%.

[0128] (Preparation of Water-Based Adhesive) 3 parts by mass of carboxyl-modified polyvinyl alcohol (Kuraray Co., Ltd., product name "KL-318") was dissolved in 100 parts by mass of water, and the resulting aqueous solution was mixed with a polyamide epoxy additive (Taoka Chemical Co., Ltd., product name "Sumirez Resin (registered trademark) 650 (30)"), which is a water-soluble epoxy resin. 」 Aqueous solution having a solid content of 30% by weight) was added in an amount of 1.5 parts by mass to prepare a water-based adhesive.

[0129] (Protective film A and release film B) As the protective film A, a film (manufactured by Nippon Paper Industries Co., Ltd., product name "COP25ST-HC") was used, in which a hard coat layer having a thickness of 3 μm was formed on a stretched film made of a cyclic polyolefin resin having a thickness of 25 μm. A triacetyl cellulose film (manufactured by Fujifilm Corporation, "TD80UL") was used as the release film B. The release film had a thickness of 80 μm and a moisture permeability of 502 g / m 2 -It was 24 hours.

[0130] (Preparation of single-sided protective polarizing plate) The prepared polarizer was continuously transported, and the protective film A was continuously unwound from the roll of the protective film A, and the release film B was continuously unwound from the roll of the release film B. A water-based adhesive was injected between the polarizer and the corona-treated protective film A, and pure water was injected between the polarizer and the release film B, and the laminated film was passed through a lamination roll to obtain a laminated film consisting of the protective film A / water-based adhesive / polarizer / pure water / release film B. The laminated film was transported and subjected to a heat treatment at 80°C for 300 seconds in a drying furnace to dry the water-based adhesive and to volatilize and remove the pure water between the polarizer and the release film B, thereby obtaining a single-sided protected polarizing plate with a release film. The release film B was peeled off from the single-sided protected polarizing plate with a release film to obtain a single-sided protected polarizing plate.

[0131] [Preparation of retardation laminate] (Preparation of the first retardation layer) The first retardation layer was a layer that gave a retardation of λ / 4 and was composed of a first liquid crystal cured layer, which was a layer of cured nematic liquid crystal compound, an alignment film, and a transparent substrate. The total thickness of the layer of cured nematic liquid crystal compound and the alignment layer was 2 μm.

[0132] (Preparation of the second retardation layer) As a composition for forming an alignment layer, 10.0 parts by mass of polyethylene glycol di(meth)acrylate (A-600, manufactured by Shin-Nakamura Chemical Co., Ltd.), 10.0 parts by mass of trimethylolpropane triacrylate (A-TMPT, manufactured by Shin-Nakamura Chemical Co., Ltd.), 10.0 parts by mass of 1,6-hexanediol di(meth)acrylate (A-HD-N, manufactured by Shin-Nakamura Chemical Co., Ltd.), and 1.50 parts by mass of Irgacure 907 (Irg-907, manufactured by BASF) as a photopolymerization initiator were dissolved in 70.0 parts by mass of methyl ethyl ketone solvent to prepare a coating liquid for forming an alignment layer.

[0133] A long cyclic polyolefin resin (COP) film (manufactured by Zeon Corporation) having a thickness of 20 μm was prepared as a substrate film, and the coating liquid for forming an alignment layer was applied to one side of the substrate film using a bar coater.

[0134] After the coating layer was heat-treated at 80°C for 60 seconds, it was exposed to ultraviolet light (UVB) at 220 mJ / cm 2 The composition for forming the alignment layer was polymerized and cured by irradiation to form an alignment layer having a thickness of 2.3 μm on the substrate film.

[0135] As a composition for forming a retardation layer, 20.0 parts by mass of a photopolymerizable nematic liquid crystal compound (RMM28B, manufactured by Merck) and 1.0 part by mass of Irgacure 907 (Irg-907, manufactured by BASF) as a photopolymerization initiator were dissolved in 80.0 parts by mass of propylene glycol monomethyl ether acetate solvent to prepare a coating liquid for forming a retardation layer.

[0136] A coating solution for forming a retardation layer was applied onto the previously obtained alignment layer, and the coating layer was subjected to a heat treatment at a temperature of 80° C. for 60 seconds. Then, ultraviolet rays (UVB) were applied at 220 mJ / cm 2 The retardation layer-forming composition was polymerized and cured by irradiation to form a second liquid crystal cured layer having a thickness of 0.7 μm on the alignment layer. In this way, a second retardation layer having a thickness of 3 μm and consisting of the alignment layer and the retardation layer was obtained on the substrate film.

[0137] (Preparation of Retardation Laminate) The first retardation layer and the second retardation layer were bonded together with an ultraviolet-curing adhesive (thickness 1 μm) so that the liquid crystal layer surface (the surface opposite to the substrate film) of each layer was bonded. Then, the ultraviolet-curing adhesive was cured by irradiation with ultraviolet light to produce a retardation laminate including two retardation layers, the first retardation layer and the second retardation layer. The thickness of the retardation laminate including the first retardation layer, the ultraviolet-curing adhesive layer, and the second retardation layer was 6 μm.

[0138] (1st adhesive layer) Adhesive layer (1): moisture permeability 160g / (m 2 A 25 μm thick film was prepared. Adhesive layer (2): moisture permeability 2000g / (m 2 A 25 μm thick film was prepared.

[0139] (Second adhesive layer) Moisture permeability 4000g / (m 2 A 5 μm thick film was prepared.

[0140] <Example 1> A second adhesive layer was attached to the polarizer side of the prepared single-sided protected polarizing plate, and the separator was peeled off. The surface of the second adhesive layer from which the separator was peeled off was attached to the first liquid crystal cured layer side of the retardation laminate from which the transparent substrate was removed, and the substrate film of the second retardation layer was peeled off. An adhesive layer (1) was attached to the surface from which the substrate film was peeled off. The polarizing plate with the adhesive layer of Example 1 had a structure as shown in FIG. 1. The results are shown in Table 1.

[0141] <Comparative Example 1> A polarizing plate with a pressure-sensitive adhesive layer was produced in the same manner as in Example 1, except that the pressure-sensitive adhesive layer (2) was used instead of the pressure-sensitive adhesive layer (1) in Example 1. The results are shown in Table 1.

[0142] [Table 1] [Explanation of symbols]

[0143] 11 protective film, 12 adhesive layer, 10 polarizer, 13 first adhesive layer, 14 second adhesive layer, 15 functional layer, 50 edge of polarizing plate with adhesive layer, 51 iodine-free region, 52 non-iodine-free region, 100 polarizing plate with adhesive layer, T transmission axis direction

Claims

1. A polarizing plate with an adhesive layer in which a protective film is disposed on only one side of a polarizer, a polarizer; and the protective film disposed on one side of the polarizer via an adhesive layer, and a second pressure-sensitive adhesive layer, a functional layer, and a first pressure-sensitive adhesive layer, in this order, on the other side of the polarizer; the second adhesive layer is disposed directly on the polarizer; The functional layer is a single layer of a liquid crystal cured layer alone, or a multilayer composed of a liquid crystal cured layer and one or more layers selected from the group consisting of a liquid crystal cured layer, an alignment layer, and an attachment layer, the polarizer is a hydrophilic polymer film having iodine adsorbed thereon; The first pressure-sensitive adhesive layer has a moisture permeability of 500 g / (m 2 ・day) or less, the second pressure-sensitive adhesive layer has a moisture permeability of 4000 g / (m2·day) or more at a temperature of 40° C. and a relative humidity of 90% R.H.; The thickness of the first pressure-sensitive adhesive layer is 10 μm or more, The second pressure-sensitive adhesive layer has a thickness of 7 μm or less.

2. 2 . The polarizing plate with a pressure-sensitive adhesive layer according to claim 1 , wherein the first pressure-sensitive adhesive layer is a pressure-sensitive adhesive layer formed from a rubber-based pressure-sensitive adhesive containing polyisobutylene and a hydrogen abstraction type photopolymerization initiator.

3. The polarizing plate with a pressure-sensitive adhesive layer according to claim 1 , wherein the first pressure-sensitive adhesive layer is a pressure-sensitive adhesive layer containing a polyolefin resin.

4. The pressure-sensitive adhesive layer-attached polarizing plate according to claim 3 , wherein the polyolefin resin comprises an amorphous polypropylene resin.

5. The polarizing plate with a pressure-sensitive adhesive layer according to any one of claims 1 to 4, wherein the protective film is a film made of a cyclic polyolefin resin.

6. The polarizing plate with a pressure-sensitive adhesive layer according to any one of claims 1 to 5, wherein the functional layer includes a first liquid crystal cured layer and a second liquid crystal cured layer.

7. A laminate for a flexible image display device, comprising the pressure-sensitive adhesive layer-attached polarizing plate according to any one of claims 1 to 6, and a front panel or a touch sensor.

8. An image display device comprising the pressure-sensitive adhesive layer-attached polarizing plate according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Adhesion type polarizing plate and image display device

    JP2012247574A

  • Method of producing transfer body for optical film, method of producing optical film, transfer body for optical film, optical film and image display device

    JP2015007700A

  • Polarizing film with adhesive layer, optical member, and image display device

    JP2017058519A

  • Optical film for organic el display devices, polarizing film for organic el display devices, polarizing film with adhesive layer for organic el display devices, and organic el display device

    JP2017203835A

  • Rubber-based adhesive composition, rubber-based adhesive layer, adhesive film, optical film with rubber-based adhesive layer, optical member, and image display device

    JP2018039863A